Expressions of ageism during the pandemic as perceived by older persons - Ana Luiza Blanco; Samila Sathler Tavares Batistoni; Daniella Pires Nunes (Brazilian Society of Geriatrics and Gerontology, 2023)
Objective: To describe expressions of ageism as perceived by older persons during the COVID-19 pandemic. Methods: Cross-sectional, exploratory, and descriptive study, including 134 older adults who answered a digital questionnaire, between January and July 2022. A word cloud was used to identify stereotypes. Prejudice was assessed using the Anxiety about Aging scale and discrimination was measured using the Ageism Survey. In addition, a semi-structured questionnaire was used to identify the types of discrimination experienced in the pandemic. Results: Older persons tend to reproduce stereotypes associated with experience and wisdom, with the presence of biopsychosocial changes and dependence, and enjoyment of life. Most older persons reported discrimination (93.50%), especially perceived through "telling jokes about older persons" (72.39%). In the pandemic setting, the most perceived discriminatory manifestations referred to policies, practices, or norms related to the pandemic (38.06%) and when reading and watching news in the newspaper, the Internet, and television (35.07%). Conclusion: The findings suggest that older persons experienced ageism during the pandemic and show the need for programs and policies aimed at education on ageing, so as to reduce the stigmas of old age and discrimination, aiming to foster healthy ageing.